Cardiovascular pathology in patients with human immune deficiency virus infection - Valenzuela-Rodríguez, Germán (2012)
Human immunodeficiency virus (HIV) infection increases both morbidity and mortality by inducing severe immunosupression that generates opportunistic infections. Following use of high active antiretroviral therapy (HAART) in infected patients, infection-related mortality has decreased and both survival and cardiovascular disease have increased. The etiology of cardiovascular disease could be related to either infection itself, proatherogenic conditions associated with antiretroviral therapy or other adverse events caused by these therapies or by combination with other drugs. As most conditions associated with cardiovascular disease have an acute onset, we present this review for their recognition in the emergency ward, choosing opportune treatment and excluding inappropiate ones.